Use of home oxygen for children in England and Wales. Issue 4 (3rd June 2010) - Primhak, R A; Hicks, B; Shaw, N J; Donaldson, G C; Balfour-Lynn, I M
Abstract : Background: With the introduction of a standardised ordering system in February 2006, the opportunity arose to collect data on children requiring home oxygen in England and Wales. The authors' aim was to determine the incidence and patterns of home oxygen prescribing. Methods: A paediatric home oxygen clinical network and the Children's Home Oxygen Record Database were established. During a 3-year period (February 2006 to January 2009), prescribers were requested to submit copies of the Home Oxygen Order Forms. In addition, anonymised point prevalence data on all patients currently receiving home oxygen in June 2007 were obtained from the four provider companies. Results: Children's Home Oxygen Record Database— Forms were analysed for 888 children <16 years (58% boys) with a median age of 4.1 months; 656 (74%) were <1 year. 541 (68%) had a diagnosis of chronic neonatal lung disease; 53 (7%), neurodisability; and 49 (6%), cardiac disease. Order forms were often incomplete, and prescribing practice was variable. Provider's cross-sectional survey —There were 3338 children <16 years, representing 4% of all patients on home oxygen. Median age was 3.1 years with a peak at 6 months. The prevalence for paediatric home oxygen use in England and Wales was 0.33 per 1000, with a peak of 1.08 per 1000 for those <1 year. Marked regional variation was noted. Conclusions: This is the first national dataset available for children prescribed home oxygen in England and Wales. The study emphasises the need for a coordinated approach to home oxygen prescribing and justifies the recent publication of evidence-based guidelines.